2011
DOI: 10.1038/jp.2011.96
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity simulator technology may not be superior to traditional low-fidelity equipment for neonatal resuscitation training

Abstract: Objective: Despite completing accredited resuscitation training, neonatal trainees often feel unprepared to deal with real-life clinical emergencies. High-fidelity simulator (HFS) technology offers the potential of recreating a realistic stressful clinical environment to aid training and evaluation. To date, there are limited data examining the physiological impact of this training modality in comparison to less costly alternatives. The objective of this study was to compare the effects of low-fidelity simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 20 publications
1
87
0
2
Order By: Relevance
“…When inductively searching for conceptual themes shared across studies, we identified 7 studies comparing high with low physical realism simulation as part of the educational intervention, and conducted a metaanalysis pooling the results of these studies. [26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
See 1 more Smart Citation
“…When inductively searching for conceptual themes shared across studies, we identified 7 studies comparing high with low physical realism simulation as part of the educational intervention, and conducted a metaanalysis pooling the results of these studies. [26][27][28][29][30][31][32] We narratively discuss the other studies with nonrecurrent themes. [33][34][35][36][37][38][39][40][41][42][43] …”
Section: Synthesis: Comparison Of Simulation Versus Other Types Of Tesmentioning
confidence: 99%
“…Seven studies [26][27][28][29][30][31][32] compared the use of high versus low physical realism simulators for TES as an educational modality (Fig 4). Meta-analysis of these studies revealed pooled effects of small magnitude favoring high physical realism for nontime skills (4 studies; ES = 0.49; P , .001) and learner reactions (3 studies; ES = 0.70; P , .01).…”
Section: Comparison Of High Versus Low Physical Realism Simulationmentioning
confidence: 99%
“…17 Our results are similar to those in a crossover study by Finan et al who showed that performing neonatal resuscitation on a full-body infant simulator during a simulated cardiac arrest scenario was not different from performing a verbalized cardiac arrest scenario on a training infant mannequin. 18 A possible explanation for our findings and those of the previous study 18 is that, although the degree of physical fidelity differed between the two scenarios, psychological fidelity may be equally high for both. Psychological fidelity involves the extent to which participants engage in tasks that generate actions and processing demands that are similar to those in the clinical environment.…”
Section: Discussionmentioning
confidence: 44%
“…In task domains where life and death are at stake, a high degree of psychological fidelity can achieve a level of stress closer to that experienced in the real-life situation. This view is supported by the study of Finan et al 18 who showed that the level of stress cortisol was similarly elevated in both NCS and CS, suggesting that psychological fidelity was high in both scenarios. There is some evidence to suggest that there can be a disconnect between psychological and physical fidelity and that psychological fidelity may be a more important factor in influencing the performance of procedural tasks.…”
Section: Discussionmentioning
confidence: 57%
“…6 A strategy that purports to increase affective realism by using high-fidelity simulation instead of low-fidelity simulation has also been used as an intervention to reduce stress in resuscitation scenarios. 17 It is known that a certain degree of stress during training can improve performance and can decrease performance-related anxiety. However, the study did not demonstrate the effective use of high-fidelity simulation over low-fidelity simulation use in terms of stress modification.…”
Section: Emotional Training Strategies In Simulationmentioning
confidence: 99%